Environmental education : training of teacher educators, curriculum developers, and educational planners and administrators - Usha Nayar; Mangalagiri, Anjana, 1953- (UNESCO-UNEP International Environmental Education Programme, 1988)
Papers presented at a consultative meeting organized by the National Institute of Educational Planning and Administration, New Delhi, with reference to India and South Asia; includes a bibliography on environmental education.